A Cross Sectional Study of Antiphospholipid-protein Antibodies in Patients with Venous Thromboembolism - Pasquier, Elisabeth; Amiral, Jean; Martin, Luc de Saint; Mottier, Dominique (Thrombosis and Haemostasis, 2001)
Objective: To look for an association between venous thromboembolism (VTE) and antiphospholipid antibodies (aPL) in patients without Systemic Lupus Erythematosus (SLE) when implementing, beside conventional assays, new tests for aPL screening directed towards purified proteic targets. Methods: We conducted a cross-sectional, hospital-based study of consecutive unselected outpatients. We compared VTE+ patients to VTE- among 398 consecutive unselected outpatients referred for clinical suspicion of VTE. To detect aPL, the following ELISAs were performed : 1) a conventional standardized ELISA 2) an improved APA assay, 3) an anti-Beta2GPI ELISA, 4) an anti-Annexin V ELISA, 5) an anti-Prothrombin ELISA. We sought an association between VTE and aPL through a quantitative (t-test) and a qualitative comparison (chi-square test, according to the cut-off values set as the 95th percentile of aPL distribution). First we conducted an analysis of all patients. Then we stratified them into 2 subgroups, with or without a wellknown risk factor for VTE (prolonged immobilization >72h, surgery or trauma within the past three months, current malignancy). Results: 61% of patients were classified as VTE-positive. Before stratification, we did not find any significant association between the VTE status and aPL. However, after stratification, in the subgroup without risk factors for VTE, the frequency of positive values as regards the anti Prothrombin antibodies detection was significantly higher in VTE+ patients (p = 0,04). Conclusion: The presence of anti Prothrombin antibodies might be an independent risk factor of VTE. However systematic screening for aPL in non SLE patients referred for VTE suspicion at the time of the thromboembolic event has little clinical relevance.
Keywords: Venous thrombo-embolism; anticardiolipin antibodies; anti annexin V antibodies; anti prothrombin antibodies; anti Beta2GPI antibodies